Bioabsorbable nerve conduits coated with induced pluripotent stem cell‐derived neurospheres enhance axonal regeneration in sciatic nerve defects in aged mice. Issue 5 (9th September 2017) - Yokoi, Takuya; Uemura, Takuya; Takamatsu, Kiyohito; Shintani, Kosuke; Onode, Ema; Okada, Mitsuhiro; Hidaka, Noriaki; Nakamura, Hiroaki
Abstract: Aging influences peripheral nerve regeneration. Nevertheless, most basic research of bioabsorbable nerve conduits including commercial products have been performed in very young animals. Results from these studies may not provide information about axonal regeneration in aged tissue, because young nerve tissue holds sufficient endogenous potential for axonal regeneration. The clinical target age for nerve conduit application is most likely going to increase with a rapidly growing elderly population. In the present study, we examined axonal regeneration after sciatic nerve defects in aged and young mice. 5‐mm sciatic nerve defects in young (6 weeks old) and aged (92 weeks old) mice were reconstructed using nerve conduits (composed of a poly lactide and caprolactone) or autografts. In addition, in aged mice, sciatic nerve defects were reconstructed using nerve conduits coated with mouse induced pluripotent stem cell (iPSc)‐derived neurospheres. Using electrophysiological and histological techniques, we demonstrated axonal regeneration was significantly less effective in aged than in young mice both for nerve conduits and for nerve autografts. However, despite the low regenerative capacity of the peripheral nerve in aged mice, axonal regeneration significantly increased when nerve conduits coated with iPSc‐derived neurospheres, rather than nerve conduits alone, were used. The present study shows that aging negatively affects peripheral nerve regeneration based on nerve conduits in mice. However, axonal regeneration using nerve conduits was improved when supportive iPSc‐derived neurospheres were added in the aged mice. We propose that tissue‐engineered bioabsorbable nerve conduits in combination with iPSc‐derived neurospheres hold therapeutic potential both in young and elderly patients. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1752–1758, 2018.